2017
DOI: 10.1038/cddis.2017.479
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-223 upregulated by MYOD inhibits myoblast proliferation by repressing IGF2 and facilitates myoblast differentiation by inhibiting ZEB1

Abstract: Skeletal muscle differentiation can be regulated by various transcription factors and non-coding RNAs. In our previous work, miR-223 is differentially expressed in the skeletal muscle of chicken with different growth rates, but its role, expression and action mechanism in muscle development still remains unknown. Here, we found that MYOD transcription factor can upregulate miR-223 expression by binding to an E-box region of the gga-miR-223 gene promoter during avian myoblast differentiation. IGF2 and ZEB1 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 51 publications
4
62
1
Order By: Relevance
“…Western blot was performed as previously described [47]. The following antibodies were used: anti-c-Myc (sc-42, Santa Cruz Biotechnology, CA, USA), anti-p38α (sc-271120, Santa Cruz Biotechnology), anti-p-p38 (sc-166182, Santa Cruz Biotechnology), anti-ERK (sc-376852, Santa Cruz Biotechnology), anti-p-ERK (sc-7383, Santa Cruz Biotechnology), anti-p-JNK (sc-6254, Santa Cruz Biotechnology), anti-Cyclin D1 (BS2436, Bioworld, St Louis Park, MN, USA), anti-Smad2 (ab228807, Abcam, Cambridge, USA), anti-p-Akt1/2/3 (sc-271966, Santa Cruz Biotechnology), anti-Wnt3 (ab50341, Abcam) and anti-Tubulin (BS1482M, Bioworld).…”
Section: Immunoblotting and Immunofluorescencementioning
confidence: 99%
“…Western blot was performed as previously described [47]. The following antibodies were used: anti-c-Myc (sc-42, Santa Cruz Biotechnology, CA, USA), anti-p38α (sc-271120, Santa Cruz Biotechnology), anti-p-p38 (sc-166182, Santa Cruz Biotechnology), anti-ERK (sc-376852, Santa Cruz Biotechnology), anti-p-ERK (sc-7383, Santa Cruz Biotechnology), anti-p-JNK (sc-6254, Santa Cruz Biotechnology), anti-Cyclin D1 (BS2436, Bioworld, St Louis Park, MN, USA), anti-Smad2 (ab228807, Abcam, Cambridge, USA), anti-p-Akt1/2/3 (sc-271966, Santa Cruz Biotechnology), anti-Wnt3 (ab50341, Abcam) and anti-Tubulin (BS1482M, Bioworld).…”
Section: Immunoblotting and Immunofluorescencementioning
confidence: 99%
“…Studies have shown that miR-223 participates in the regulation of cardiomyocyte glucose metabolism, myoblast proliferation and differentiation, esophageal squamous cell carcinoma and human granulopoiesis [11][12][13]. In the osteogenic differentiation of hBMSCs, miR-223 was found to act as both a positive and a negative regulator, suggesting its potential in the treatment of bone-related diseases [14].…”
Section: Introductionmentioning
confidence: 99%
“…For primary myoblast isolation, at least six embryos at embryo day 11 (E11) were used in each experiment. The sex of each embryos was determined by PCR with the sex-specific primers ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chicken embryo fibroblast cell line was cultured in high-glucose Dulbecco’s modified Eagle’s medium (Gibco) with 10% fetal bovine serum and 0.2% penicillin/streptomycin. The isolation and culture of chicken primary myoblasts were carried out as previously described ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%